2013
DOI: 10.1590/1679-775720130002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Class II treatment with the Bionator followed by fixed appliances

Abstract: ObjectiveThis prospective study assessed the stability of Class II treatment with the Bionator, followed by fixed appliances, 10 years after treatment. Material and MethodsThe experimental group comprised 23 patients of both sexes (10 boys, 13 girls) at a mean initial age of 11.74 years (late mixed or early permanent dentitions), treated for a mean period of 3.55 years who were evaluated at three stages: initial (T1), final (T2) and long-term posttreatment (T3). A total of 69 lateral cephalograms were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…, 13 , 20 , 38 - 40 This means that although some small differences may exist in their mode of action, regarding the amount of dental skeletal changes, they will produce positive significant changes in the overjet and overbite, which are some of the important aspects to be corrected in many Class II malocclusions 7 13 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…, 13 , 20 , 38 - 40 This means that although some small differences may exist in their mode of action, regarding the amount of dental skeletal changes, they will produce positive significant changes in the overjet and overbite, which are some of the important aspects to be corrected in many Class II malocclusions 7 13 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of this is clear with intervention required to address class II malocclusion, while early achievement of a class I incisor relationship is likely to be relatively stable over a period of growth. The latter has variously been confirmed with antero-posterior correction among the more stable orthodontic changes [22,23].…”
Section: Discussionmentioning
confidence: 78%
“…[10][11][12] Other studies reported similar results on long-term outcomes of bionator treatment based on measurements of dental casts. 15 However, this study was the first to evaluate long-term effects of bionator treatment without follow-up treatment with fixed appliances, thus enabling an assessment of the long-term stability of bionator therapy itself, taking physiological changes due to aging into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]13,14 Francisconi et al reported that therapy with a bionator followed by fixed appliances produced favorable results in apical base and molar relationships, overjet, and overbite that remained stable 10 years posttreatment. 15 Only a few studies, however, investigated long-term changes of dental arches after functional treatment more than 15 years after treatment. There is no study assessing long-term stability of bionator therapy that was not supplemented by fixed appliances.…”
Section: Introductionmentioning
confidence: 99%